A systems thinking approach for examining the turning points in the Finnish public sport policy - Lehtonen, Kati; Uusikylä, Petri; Jalonen, Harri; Lappalainen, Sari (Frontiers media, 2025)
Background and study aim: This study proposes a longitudinal analysis of the Finnish public sports policy and explores the dynamics between turning points from a systems thinking perspective. We argue that a better understanding of the dynamics and relationships between turning points, interruptions, and new paths in the policy process can guide future options for public sports policies. Material and methods: Documentary and interview-based materials were used as data and timeline mapping as an analyzing method. Results: Our results show that there have been four turning points during the review period. The first turning point in the early 1990s is fundamental and it had large-scale effects on the direction of sport policy. The other three are moderate in their nature, smoothly affecting the direction of the policy process. Policy venues have changed from theme-specific working groups to permanent entities operating within the state administration. At the same time, party politics has returned to politics, a phenomenon that seems at odds with the first turning point. Conclusions: For decision-makers and practitioners, the current policy space requires increasing ability to make decisions on a long-term basis despite several interests, increasing complexity of governance and the needs of differentiated subsystems.
Keywords: sport policy; complexity; timeline mapping; turning point; systems thinking; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|